Two Strategies Of Agent-Based Modelling Application For Management Of Lakeland Landscapes At A Regional Scale - Giełda-Pinas, Katarzyna; Dzieszko, Piotr; Zwoliński, Zbigniew; Ligmann-Zielińska, Arika (Quaestiones Geographicae, 2015)
This work presents two different strategies of ABM for management of selected lakeland landscapes and their impact on sustainable development. Two different lakeland research areas as well as two different sets of agents and their decision rules were compared. In Strategy 1 decisions made by farmers and their influence on the land use/cover pattern as well as the indirect consequence of phosphorus and nitrogen delivery to the water bodies were investigated. In this strategy, a group of farmer agents is encouraged to participate in an agri-environmental program. The Strategy 2 combines the decisions of farmers, foresters and local authorities. The agents in the model share a common goal to produce a spatial plan. The land use/cover patterns arising from different attitudes and decision rules of the involved actors were investigated. As the basic spatial unit, the first strategy employed a landscape unit, i.e. lake catchment whereas the second strategy used an administrative unit, i.e. commune. Both strategies resulted in different land use/cover patterns and changes, which were evaluated in terms of sustainability policy. The main conclusion for Strategy 1 is that during 5 years of farmer’s participation in the agri-environmental program, there was significant decrease of nutrient leaching to the lake. The main conclusion for Strategy 2 should be stated that cooperating of the agents is better for the natural environment than the competitions between them. In both strategies, agents’ decisions influence the environment but different spatial units of analysis express this environment.